Consideraç\~oes sobre a política para atraç\~ao de investimentos externos - Renato Baumann (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The inflow of foreign investment can provide several positive economic effects. The main determining elements are related to the economic environment, but this does not mean that the government options are limited. Policy measures that affect the operation of firms have a significant weight in the decision process by potential investors. This text aims at contributing to the debate about the Brazilian policy towards the attraction of foreign direct investment, emphasizing a few dimensions that have been less considered so far, but should be a systematic part of such policy.
Keywords: F13; F21; F43; F63; 330; foreign direct investment; responsible business conduct; ombudsman for investments